Local knowledge system in music education culture at indigenous community Kampung Naga Tasikmalaya Regency (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This study aims to investigate the teaching culture in the indigenous community. This study explores the local knowledge system in the practice of music teaching in an indigenous community of Kampung Naga, Tasikmalaya regency. This is an ethnographic research to give a detailed analysis on each case and to understand the phenomena from the point of view of the doers. This study documents the local knowledge system in music teaching culture in Kampung Naga, including nu dirampa (tried, explored), nu dirasa (perceived, contemplated), and nu nyata (used, applied). Hopefully, these findings can be the foundation of education, conservation, and innovation, and also as skills to improve the society’s welfare, not only Kampung Naga society, but also other societies, especially in the context of education at school.